Policy on the Implementation of Restorative Justice for Prisoners in the Implementation of the Correctional System - Hartarto, Nurcahyo Dwi; Masu, Reny Rebeka; Medan, Karolus Kopong (Journal of Law Science, 2025)
Restorative Justice is an alternative method of resolving criminal cases within the criminal justice system that can be implemented at every stage of legal proceedings are pre-adjudication, adjudication, and post- adjudication. Corrections constitute a component of the criminal justice system at the post-adjudication stage, where restorative justice can also be applied to inmates serving sentences in correctional institutions. The rehabilitation programs currently implemented in correctional facilities still rely on the concept of retributive theory, which focuses primarily on the offender, leaving the victim’s interests largely unaddressed. The implementation of restorative justice in correctional institutions aims to restore the relationship between the offender and the victim through mechanisms such as compensation, reconciliation efforts, and rehabilitation. Inmates who have undergone restorative justice processes within correctional institutions may be eligible for release during the assimilation phase without having to wait for full reintegration. The government is expected to issue a comprehensive regulation for all law enforcement agencies as a foundational guideline for implementing restorative justice within the criminal justice system, along with technical guidelines or instructions that serve as a legal framework for correctional officers in applying restorative justice to inmates in correctional facilities